Modelling the Risks of the Exporter’s Company in Times of Crisis - AL- ABABNEH, Hassan Ali; TSIAPA, Andrii; RUDYK, Nataliia; KAPYRULYA, Mykhaylo; YATSUKH, Rostyslav (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025, 2025)
Exporting companies face numerous risks generated both within the country and by importing countries. Therefore, early detection and analysis of national and international risks is relevant and urgent. The aim of the study is to analyse the relationship between the volume of Ukrainian exports and macroeconomic indicators of Ukraine and importing countries. This will reveal the potential impact of fluctuations in these indicators on changes in the level of major export risks. The study employed economic and statistical analysis, correlation and regression analyses. The study determined the key influencing factors on the activities of Ukrainian exporting companies depending on the importing country. The level of gross domestic product (GDP) per capita is an important factor influencing the volume of exports from Ukraine to Poland, Spain, and Germany. Exports to Poland are also closely correlated with fluctuations in the local currency. Exports to China and Turkey do not significantly depend on changes in local macroeconomic indicators. Macroeconomic indicators of Ukraine - GDP per capita, customs, as well as other import duties and taxes on international trade - significantly affect the total volume of exports. The obtained results and drawn conclusions are of practical importance for Ukrainian exporters in terms of raising awareness of the described risks, and the recommendations provided on the basis of the study will contribute to their mitigation. The prospect of further research is to identify differences in the exporters’ risks depending on the field of their activity.